Antiviral activity against porcine epidemic diarrhea virus of Pogostemon cablin polysaccharide. (15th September 2020) - Chen, Yun; Luo, Qiyuan; Li, Shanman; Li, Chengheng; Liao, Suya; Yang, Xin; Zhou, Ruigang; Zhu, Yongjian; Teng, Ling; Chen, Huricha; Yang, Yuhui
Abstract: Ethnopharmacological relevance: The dry overground parts of Pogostemon cablin (Blanco) Benth. is widely used in China as a traditional Chinese medicine for the treatment of diarrhea, vomiting, nausea and fever. Polysaccharide is an important component of Pogostemon cablin (Blanco) Benth. but has not been studied. Pogostemon cablin (Blanco) Benth. is used to treat porcine epidemic diarrhea. But it is not known whether Pogostemon cablin polysaccharides (PCPs) has the antiviral activities against porcine epidemic diarrhea virus (PEDV). Aim of the study: The purpose of present study is to investigate the structural characterization and the anti-PEDV activities of PCPs. Materials and methods: PCPs were prepared by water extraction and alcohol precipitation method and purified with DEAE-52 cellulose column and Sephadex G-100 column. Then, the structural characterization of the polysaccharides including the infrared spectrum, molecular weight and monosaccharide composition were analyzed. Afterwards, the antiviral effect of PCPs against PEDV on IPEC-J2 cells was studied by MTT method and real-time PCR method. Additionally, the effects of PCPs on PEDV adsorption, penetration and replication were analyzed by real-time PCR method. Furthermore, we also investigate whether the anti-oxidative effects of PCPs were important to the anti-PEDV activities. Results: Four polysaccharides were obtained and named as PCP1.1 (31.3 kDa), PCP1.2 (3.5 kDa), PCP2.1 (9.1 kDa) and PCP2.2 (8.3 kDa). PCP1.1, PCP1.2 and PCP2.1 were composed of fucose, arabinose, galactose, glucose, mannose, galacturonic acid and glucuronic acid; and PCP2.2 was composed of arabinose, galactose, glucose, galacturonic acid and glucuronic acid. All PCPs showed anti-PEDV activities. PCP1.1 and PCP1.2 inhibited PEDV replication, while PCP2.1 and PCP2.2 inhibited PEDV penetration and replication. All PCPs showed anti-oxidative effects, which were important to the anti-PEDV activities. Conclusions: The treatment effect of Pogostemon cablin (Blanco) Benth. on porcine epidemic diarrhea might be related to the anti-PEDV effect of PCPs. Furthermore, the anti-oxidative effects of PCPs play important roles in their antiviral activities against PEDV. Graphical abstract: Image 1 Highlights: This is the first report of the polysaccharides in Pogostemon cablin (Blanco) Benth. Four polysaccharides were obtained and named as PCP1.1, PCP1.2, PCP2.1 and PCP2.2 The structural characterizations of PCPs were first reported. Antiviral effects against porcine epidemic diarrhea virus of PCPs were first studied. All the four PCPs showed antiviral abilities and the ability of PCP1.1 was the best.